Fairness and Freight-Handlers : Local Labor-Market Conditions and Wage-Fairness Perceptions in a Trucking Firm - Eric A. Verhoogen; Stephen V. Burks; Jeffrey P. Carpenter (Institute for the Study of Labor (IZA), 2004)
This paper draws on evidence from an internal attitude survey in the freight-handling terminals of a unionized trucking firm to investigate the effect of local labor market conditions on employee wage-fairness perceptions. The key element of our research design is that local managers have no discretion to vary wage rates in response to local labor market conditions; local economic shocks thus generate exogenous variation in the attractiveness of the wage paid by the firm relative to employees? options in the outside labor market. We find robust associations between two indicators of local conditions – the rate of unemployment and the wages of similar workers in the outside market – and the wage-fairness perceptions of employees in the firm, which we argue reflects a causal relationship. As an extension, we relate the changes in local conditions and fairness perceptions to changes in employee performance, as measured by the rate of disciplinary dismissals. We find suggestive evidence that increased local unemployment leads to improved employee performance, and, conditional on a particular assumption about the mechanism through which local conditions affect performance, that increases in wage-fairness perceptions lead employees to supply more effort.
Keywords: D23; Z13; J41; 330; fairness; gift exchange; reference point; efficiency wage; Lohn; Gerechtigkeit; Meinung; Regionaler Arbeitsmarkt; Regionale Arbeitslosigkeit; Güterverkehrsgewerbe; Schätzung; Vereinigte Staaten